Cote d'Ivoire Jobs Diagnostic : Employment, Productivity, and Inclusion for Poverty Reduction - Christiaensen, Luc; Premand, Patrick (World Bank, Washington, DC, 2017)
After a decade of crisis and stellar economic growth over the past five years, Côte d’Ivoire has now set its sight on becoming an emerging economy. Improving prospects for productive employment will be essential for socially sustainable growth and poverty reduction. The "Cote d'Ivoire Jobs Diagnostic: Employment, Productivity, and Inclusion for Poverty Reduction" report provides a comprehensive and multi-sectoral empirical analysis of employment challenges and opportunities to inform strategies and policy actions in Côte d’Ivoire. The report aims to expand policy discussions on employment from a focus on the number of jobs and unemployment to a broader attention on the quality, productivity and inclusiveness of jobs. It makes the case for a jobs strategy with a sharper poverty lens that would focus on raising labor productivity in agriculture and informal off-farm employment to foster structural transformation, while, in parallel, pursuing longer-term goals of expanding the thin formal sector.